2012
DOI: 10.1111/j.1365-2966.2012.21848.x
|View full text |Cite
|
Sign up to set email alerts
|

SPIDER - VII. Revealing the stellar population content of massive early-type galaxies out to 8Re

Abstract: Radial trends of stellar populations in galaxies provide a valuable tool to understand the mechanisms of galaxy growth. In this paper, we present the first comprehensive analysis of optical–optical and optical–NIR colours, as a function of galaxy mass, out to the halo region (8Re) of early‐type galaxies (ETGs). We select a sample of 674 massive ETGs (M★ ≳ 3 × 1010 M⊙) from the Sloan Digital Sky Survey (SDSS)‐based SPIDER survey. By comparing with a large range of population synthesis models, we derive robust c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
98
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 105 publications
27
98
2
Order By: Relevance
“…A.1). This is the normal behavior for early-type galaxies (e.g., La Barbera et al 2012) and is compatible with the negligible age and metalicity gradients found by Reda et al (2007) inside 0.5R e . No dusty features are visible.…”
Section: Galaxy Surface Brightness and Colorssupporting
confidence: 59%
“…A.1). This is the normal behavior for early-type galaxies (e.g., La Barbera et al 2012) and is compatible with the negligible age and metalicity gradients found by Reda et al (2007) inside 0.5R e . No dusty features are visible.…”
Section: Galaxy Surface Brightness and Colorssupporting
confidence: 59%
“…Negative metallicity gradients extending to the outer radii are found in most earlytype galaxies (e.g. Baes et al 2007;La Barbera et al 2012). Flat and positive [α/Fe] gradients are commonly found in early-type galaxies at small radii (Kuntschner et al 2010), and there is evidence that, at least, metallicity gradients extend to larger radii (La Barbera et al 2012;Pastorello et al 2014).…”
Section: The Extended Symmetric Halomentioning
confidence: 99%
“…These results are in contrast with recent results by Greene et al (2012Greene et al ( , 2013: for a sample of ∼30 early type galaxies they find at 2 R eff an old (10 Gyr) stellar population with [Fe/H] ∼ −0.5, and interpret this as the stellar outskirts of these galaxies being built up through minor mergers. Coccato et al (2010), La Barbera et al (2012), Montes et al (2014) observing a few massive ellipticals reported a decline of the metallicity to under solar in an old stellar population in their outskirts (≥10 R eff ) suggesting that these galaxies are formed in two phases, the central core through major mergers, and through minor mergers farther out. However, other recent works show examples of ETG with an old and metal-rich stellar population and a very shallow metallicity gradient up to 3 R eff in contrast with the results by Greene et al (2012Greene et al ( , 2013.…”
Section: Implications From This Work and Comparisonmentioning
confidence: 99%